The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1161/circheartfailure.119.006513
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Wearable Monitoring Analytics Predict Heart Failure Hospitalization

Abstract: Background: Implantable cardiac sensors have shown promise in reducing rehospitalization for heart failure (HF), but the efficacy of noninvasive approaches has not been determined. The objective of this study was to determine the accuracy of noninvasive remote monitoring in predicting HF rehospitalization. Methods: The LINK-HF study (Multisensor Non-invasive Remote Monitoring for Prediction of Heart Failure Exacerbation) examined the performance of a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(179 citation statements)
references
References 18 publications
4
146
0
5
Order By: Relevance
“…To overcome the limitations of single channel monitoring, multiparameter monitoring wearable devices are being investigated. The LINK-HF study used a multiparameter patch sensor with ECG monitoring, intrathoracic impedance detection, accelerometry and temperature sensor on 100 patients with heart failure [ 51 ••]. A machine learning algorithm was then used on the data to create a personalised baseline for each individual, and then, a further predictive algorithm for decompensation was derived which demonstrated a sensitivity of 76% and specificity of 85% for a decompensation alert 10 days before the event.…”
Section: Direct-to-consumer Devices and Their Potential Usementioning
confidence: 99%
“…To overcome the limitations of single channel monitoring, multiparameter monitoring wearable devices are being investigated. The LINK-HF study used a multiparameter patch sensor with ECG monitoring, intrathoracic impedance detection, accelerometry and temperature sensor on 100 patients with heart failure [ 51 ••]. A machine learning algorithm was then used on the data to create a personalised baseline for each individual, and then, a further predictive algorithm for decompensation was derived which demonstrated a sensitivity of 76% and specificity of 85% for a decompensation alert 10 days before the event.…”
Section: Direct-to-consumer Devices and Their Potential Usementioning
confidence: 99%
“…In the heart failure care field, wearable sensors coupled with ML analytics can be potentially used to improve clinical outcomes and reduce hospitalizations [ 36 38 ]. Heart failure is a chronic disease with acute exacerbations that reports high rates of hospitalization and mortality year after year (one-year hospital readmission rate of more than 50%, and one-year mortality rates of 30%) [ 39 ] and involves a worldwide expenditure of around $31 billion [ 40 ] yearly.…”
Section: Electronic Health: Mobile Health and Iotmentioning
confidence: 99%
“…Due to the high cost of hospitalizations (the average length is 5–10 days) [ 41 ] and the high rates of morbidity and mortality (especially between the elderly population), the potential of IoT-based devices stands out. In the LINK-HF study [ 36 ], it was demonstrated that machine learning models that use data from VitalPatch®, a wearable sensor, can more accurately forecast heart failure exacerbation than invasive devices. The sensor layer used in the mentioned study was made up of a multisensory patch placed on the chest that recorded physiological data.…”
Section: Electronic Health: Mobile Health and Iotmentioning
confidence: 99%
“…Es gelang sogar, das Risiko für eine erst Jahre später entstandene Herzinsuffizienz bei Patienten zu ermitteln, die zum Zeitpunkt der EKG-Aufzeichnung noch eine normale Pumpfunktion aufwiesen [3]. Mithilfe von Informationen aus einem Brustpatch, der neben EKG auch Temperatur, Hautimpedanz und Bewegung aufzeichnet, konnte in einer Studie an Herzinsuffizienzpatienten eine kardiale Dekompensation mit einem zeitlichen Vorlauf von knapp 7 Tagen vorhersagt werden [24]. Solch ein präziser Blick in die Zukunft erlaubt eine rechtzeitige medizinische Intervention, um zukünftige kardiale Dekompensation in diesem Patientenkollektiv zu verhindern.…”
Section: Neue Parameterunclassified